Pengembangan Desain Aplikasi Daily Report dengan Pendekatan User Centered Design - Tresnawati, Dewi; Fitriani, Leni; Kamal, Muhammad Abyan; Setiawan, Asep Trisna (Jurnal Algoritma, 2024)
Independent learning is an activity carried out by students with the aim that students can explore the material provided by the lecturer. Therefore, the Daily Report application is here to help students report independent learning activities carried out by students. Problems arise when students find it difficult to use the Daily Report application due to several things such as inappropriate button placement, input form design that is too rigid and using inappropriate fonts and icons. The aim of this research is to develop the Daily Report application design by applying the user-centered design methodology. The user-centered design methodology is an application design development methodology that focuses on user needs. This research resulted in the development of the Daily Report application design with test results using the usability scale system obtaining an average usability score of 73 with a scale grade of C and an adjective rating of Good, which proves that the development of the application design makes it easier for students to use the Daily Report application.